Development Of Microcontroller-Based Dual Directional Coupler Microwave System To Measure Moisture Content Of Hevea Rubber Latex - Mohammadi, Ahmad (2009)

(untitled)
The rubber industry is one of the most important industries in South-East Asian countries and moisture content determination is the main parameter for quality inspection and process control. Developing digital, portable, accurate chip and measurement instruments certainly facilitates the trading and helps the growth of the industry. It is important that true moisture content of the rubber latex can be determined correctly and instantly to ensure a fair price quotation is given to the tapper at the rubber collection center on the same day. This thesis describes the development of digital, portable, rapid, simple to operator, chip and accurate microwave instrument to determine the total solid content (TSC) or moisture content (MC) of hevea rubber latex using microcontroller, dual directional coupler, and open-ended coaxial sensor. Various coaxial sensors were simulated using FEMLAB to study the reflection coefficient of the sensor corresponding to the total solid content of hevea rubber latex. The performance of the fabricated open-ended coaxial sensor was tested using Vector Network Analyzer (VNA) and the results then compared with commercial HP 85070B flanged sensor. The Microwave Office 2001 (MWO) was used to simulate the Dual Directional Coupler (DDC). The developed DDC was operated at 5 GHz which gave the high correlation between dielectric properties and moisture content of latex. S-parameters of the fabricated DDC were measured using VNA and they compared satisfactory to theoretical simulations. One coaxial voltage controlled oscillator was used as the signal source in the sensor system at 5 GHz. Two coaxial detectors were used to measure the coupled and reflected signals in this system. The calibration equation which relates the measured output voltages from detectors and TSC of latex was found. The whole sensor system was interfaced to an ATMega16 microcontroller. Based on the calibration equation and set-zero point, software program of the microcontroller was developed using BASCOM-AVR software to follow by calculation setup, calibration, and display the value of TSC on the LCD. The whole system was tested using diluted rubber latex with different TSCs at room temperature (25oC) and the results from standard oven drying method and this study were found in good agreement with the accuracy and reproducibility at the level of less than 0.5%.